Heterogeneous catalytic ozonation using magnetically recoverable copper ferrite for the treatment of surfactant containing laundry wastewater - Pang, Chuan Kian (2023)
Laundry detergent wastewater is a potential renewable resource that can be recycled and reused in order to mitigate water scarcity. The negative impacts of surfactant from laundry detergent wastewater on the environment, increased usage of detergent due to intense population growth, and the ineffectiveness of conventional treatment technologies, have resulted in the eutrophication of lakes and rivers. The catalytic ozonation process as one of the most effective advanced oxidation processes (AOPs) has shown tremendous potential in the treatment and reclamation of laundry wastewater as an alternative water source. In this research, a magnetically recoverable copper ferrite was prepared by the modified sol-gel method for the treatment of laundry detergent wastewater using the catalytic ozonation process. The catalyst was characterized by X-ray powder diffraction (XRD), Brunauer-Emmett-Teller (BET), X-ray photoelectron spectroscopy (XPS), field-emission scanning electron microscope (FESEM), magnetization measurements (VSM), and Fourier transform infrared (FT-IR) spectroscopy. The effects of important parameters such as catalyst dosages (0.1 to 1.5g/L), solution pH (3, 7 and 10), initial surfactant concentrations (2.5, 5.0 and 10 ppm), and ozone dosages (0.88, 3.68 and 4.88mg/min) on the efficiency of catalytic ozonation were investigated. The best conditions for surfactant removal (98.4%) were obtained at an initial surfactant concentration of 10ppm, reaction time of 30 minutes, a catalyst dosage of 0.2g/L, an initial solution pH of 7 and an ozone dosage of 3.68mg/min. At this condition, further chemical oxygen demand (COD) removal testing was determined to be 79.5%, compared to that of the ozonation process at 26.7%. The biochemical oxygen demand (BOD) removal percentages for ozonation and catalytic ozonation were 33.3% and 93.3%, respectively. The experimental data fits well with the pseudo-first-order kinetics model. The repetitive use of the catalyst showed that even after three consecutive runs, the catalytic activity had not decreased much. The utilisation of copper ferrite in catalytic ozonation encounters certain restrictions, such as the leaching of metal ions and the agglomeration of the catalyst. The quality of the treated wastewater complies with the standard approved by the Environmental Quality Acts Standard 2009. The potential reaction mechanism of catalytic ozonation utilising copper ferrite involves the integration of molecular ozone oxidation, as well as heterogeneous and homogeneous catalytic ozonation processes. Furthermore, the economical evaluation by means of the calculation of electric energy per order of pollutant removal (EE/O) indicated that the catalytic ozonation process required less electrical energy (60.31 kWhm-3order-1) compared to ozonation process (381.68 kWhm-3order-1). Overall, catalytic ozonation with copper ferrite is a feasible method for laundry detergent wastewater treatment.